2006
DOI: 10.1038/sj.eye.6702332
|View full text |Cite
|
Sign up to set email alerts
|

Vitreoretinal surgery after childhood ocular trauma

Abstract: Aim In adults modern vitreoretinal surgery allows many traumatised eyes to be salvaged. However, one third of serious eye injuries occur in the paediatric age group and trauma is a leading cause of monocular blindness in childhood. This study aims to report the indications, complications and outcomes for vitreoretinal surgical intervention after childhood ocular trauma. Methods Retrospective case note review of 61 children (age 16 years or less) undergoing vitreoretinal surgical procedures following ocular tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
41
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 21 publications
6
41
1
2
Order By: Relevance
“…In the present study, despite the high anatomical success due to improved surgical techniques, the visual outcome was low, similar to previous studies [21,24,25]. Delayed diagnosis is a significant feature of RD.…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, despite the high anatomical success due to improved surgical techniques, the visual outcome was low, similar to previous studies [21,24,25]. Delayed diagnosis is a significant feature of RD.…”
Section: Discussionsupporting
confidence: 76%
“…Many studies have confirmed the association between RD and poor prognostic features. 1,9,11,12 Photoreceptor cells are seriously injured when RD occurs, and proliferative vitreoretinopathy after RD is another factor that may cause limited postoperative vision.…”
Section: Discussionmentioning
confidence: 99%
“…14,19,23,24 We found a strong positive correlation (Po0.001) between initial and final visual acuities. Presenting visual acuity of 20/400 or less was predictive of poor visual outcome, especially in the surgical treatment group (Po0.001 and P ¼ 0.042 for surgical treatment and medical treatment groups, respectively).…”
Section: Discussionmentioning
confidence: 68%